The Influence of the Role of the Digital Economy in Advancing Economic Growth in Indonesia - eltomoro, Erik; Velicia, Gracia (Yayasan Cinta Negara Indonesia, 2025)
This study aims to evaluate the impact of the digital economy on financial inclusion in Indonesia and analyze the challenges faced in its implementation. In recent years, the rapid development of digital technology has opened up great opportunities to expand access to financial services in Indonesia, especially for people who were previously unreached by the traditional banking system. However, despite significant progress, there are still various obstacles that hinder the achievement of optimal financial inclusion, such as the digital divide, low financial literacy, and data security issues. This research uses a qualitative and quantitative approach by analyzing data from various sources, including surveys of digital financial service users, government reports, and case studies of digital financial inclusion policy implementation. The results show that the digital economy has great potential to improve financial inclusion, but the main challenges lie in the technology access gap, socio-economic inequality, and the need to strengthen data protection and transaction security regulations. Based on these findings, this study provides policy recommendations involving digital infrastructure upgrades, digital financial literacy education, and strengthened security regulations to support the achievement of greater financial inclusion in Indonesia. It also suggests further studies to understand the long-term impact of the digital economy on reducing social and economic inequality and the effectiveness of existing policies